MEMBANGUN KOMPETENSI KEWARGANEGARAAN GENERASI Z UNTUK MEMBENTUK KARAKTER BANGSA - Echa Surya Nanda Kurniawan; Nurdin Nurdin; Muhamad Subkhan; Pat Kurniati; Sri Rumiati (P2M STKIP Siliwangi, 2022)
The purpose of this study is to examine and analyze in-depth Building Citizenship Competencies of Generation Z to Shape Nation's Character which departs from the point of view of a proposition that civic competence is seen as capable of providing practical solutions that are connected with national education in Indonesia in shaping the nation's character. This study uses a qualitative method with a literature study approach, analyzing theories based on the phenomena that occur to obtain a comprehensive understanding of the Building Citizenship Competencies of Generation Z to Shape the Nation's Character. The results of the study indicate that it is necessary to apply Pancasila values in building appropriate citizenship competencies for generation Z. Generation Z who are very, creative, innovative, and informative are expected to be able to practice the values of Pancasila in building civic competence. Strengthening civic competence in generation Z needs to be strengthened and gets attention from the government. The application of Pancasila values for generation Z must be adapted to the times and current technological developments. With the right teaching methods, knowledge and methods can be transformed into technological tools that are widely used by Generation Z.